2023
DOI: 10.1007/s00382-022-06637-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the convection-permitting regional climate model CNRM-AROME41t1 over Northwestern Europe

Abstract: Since a decade, convection-permitting regional climate models (CPRCM) have emerged showing promising results, especially in improving the simulation of precipitation extremes. In this article, the CPRCM CNRM-AROME developed at the Centre National de Recherches Météorologiques (CNRM) since a few years is described and evaluated using a 2.5-km 19-year long hindcast simulation over a large northwestern European domain using different observations through an added-value analysis in which a comparison with its driv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 103 publications
6
17
0
Order By: Relevance
“…AROME and ALADIN in retrospective mode (evaluation) show correct annual cycles despite an overestimation of summer temperature both for T min and T max . Results in this area are in line with the recent evaluation of the ALADIN and AROME climate models (Lucas-Picher et al, 2023). The ALADIN RCM is generally colder than AROME, which can be explained by an effect of resolution.…”
Section: Added Value Of Cpm At the Catchment Scalesupporting
confidence: 88%
See 2 more Smart Citations
“…AROME and ALADIN in retrospective mode (evaluation) show correct annual cycles despite an overestimation of summer temperature both for T min and T max . Results in this area are in line with the recent evaluation of the ALADIN and AROME climate models (Lucas-Picher et al, 2023). The ALADIN RCM is generally colder than AROME, which can be explained by an effect of resolution.…”
Section: Added Value Of Cpm At the Catchment Scalesupporting
confidence: 88%
“…CNRM-ALADIN has been extensively used in the CORDEX framework over Europe, the Mediterranean, North America and Africa. For more details about the parameterization schemes and configurations of the last version of ALADIN, see Nabat et al (2020) and Lucas-Picher et al (2023).…”
Section: Climate Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, CP-RCMs have provided insight into precipitation extremes, especially the location and structure of Mediterranean HPEs, for example, in the eastern Mediterranean coast and the Island of Cyprus (Armon et al, 2020), Southeastern France (Fumière et al, 2020;Luu et al, 2022), the Catalonia coast (Meredith et al, 2020), the pan-Europe region (Berthou et al, 2020), the pan-Alpine region (Caillaud et al, 2021;Ban et al, 2021;Pichelli et al, 2021) and the Northwestern Europe region (Lucas-Picher et al, 2023); all these have demonstrated an added value of CP-RCMs in comparison to RCMs.…”
Section: Mediterranean Heavy Precipitation Eventsmentioning
confidence: 99%
“…Mostly based on numerical weather prediction models, CP-RCMs have a spatial resolution of a few kilometres (< 4 km), in which deep convection is explicitly resolved, instead of being parameterised (Kendon et al, 2012;Prein et al, 2015). Since the early 2010, CP-RCMs have demonstrated an improved representation of complex terrains, as well as the local-scale climate processes such as extreme precipitation (Kendon et al, 2012;Ban et al, 2015;Prein et al, 2015;Kendon et al, 2017;Fumière et al, 2020;Pichelli et al, 2021;Caillaud et al, 2021;Ban et al, 2021;Luu et al, 2022;Lucas-Picher et al, 2023), and orographically induced precipitation (Adinolfi et al, 2021;Monteiro et al, 2022). These processes are particularly relevant for simulating climate conditions over islands.…”
Section: Introductionmentioning
confidence: 99%